New Media Sebagai Strategi Komunikasi Online Pariwisata Untuk Mempromosikan Potensi Lokal Desa Wisata Sudaji - I Gede Titah Pratyaksa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This study discusses how the use of social media as a communication strategy to promote the local potential of Sudaji Tourist Village. Researchers use content analysis to collect data. As a result, there are specialties in the use of social media between Instagram and Facebook to promote the local potential of Bawean island tourism. The use of Instagram and Facebook is more generally non-segmented, although account settings can be set as personal pages, groups or fanpages. While Instagram is more specific in a visual perspective. Content with a personal perspective is more towards soft selling, content with an information perspective is more towards hard selling, while content with an activity perspective is more towards prescriptions or suggestions that are applicable to prospective tourists who will visit Sudaji Tourist Village. Sudaji Tourist Village tourism authority needs to optimize the use of social media because its openness and interactivity is very potential to increase tourist visits to Sudaji Tourist Village. Keyword: Tourism Communication, Local Potential, Sudaji Tourist Village, New Media